Rekonstruksi Maskulinitas dalam Kerangka Kapitalisme - Yuhdi Fahrimal; Asmaul Husna (Avant Garde, 2020)
The meaning of masculinity changes along with the development of technology, media growth, and social change in society. This has become a factor influencing the increasingly deep grip of global capitalism. Within the framework of global capitalism masculinity is commodified into a consumptive lifestyle. The purpose of this study is to understand the reconstruction of male body masculinity that is influenced by global capitalism. The proposed research design is a desk study method where researchers use various concepts related to (1) male body construction; (2) capitalism and the reconstruction of the male body; (3) media frame and male body image; (4) reconstruction of masculinity; and (5) gender construction in the media frame. The results of the document review show that in global capitalism, the concept of masculinity shifts to consumption which is intervened through the media. The shift in meaning and indicators of masculinity ultimately force men to change their lifestyle by consuming certain symbols, signs and values. The most extreme form of masculinity reconstruction is hyper-masculinity.